WITTGENSTEIN´S PRIVATE OBJECTS: INVESTIGATIONS 277 AND 304 - Shirley, Edward S. (Daimon Revista Internacional de Filosofia, 1990)
It is commonly thought that in Philosophical Investigations Wittgenstein denies that there are private objects of awareness in the sense of objects of which only the person experiencing them can possibly be aware. The reason for this belief is Wittgenstein´s denial that any such objects can fumish a basis for knowledge or languaje or form a screen between us an the external world. I show that he doesn´t deny there are such objects of awareness, but only that they can come between us and the world. The awareness of the objects is noncognitive - i.e., nothing can be said about them. Comparing what Wittgenstein says in paragraphs 277 and 304 I show that such objects function noncognitively as do special kinds of awareness this is and how such objects differ from sense-data and are not normally objects of awareness. Only in special situations such as that described in 277 do we become conscious of them. Finally I show that in the famous passage on page 207 Wittgenstein is denying the existence of sense-data, not of these private objects. Thus I reconcile 277 and 304 with page 207.